El génesis de la cultura represiva de México Moctezuma y Hernán Cortés - Los gemelos malditos - - Carlos, Juan Herrera (Diálogos Latinoamericanos, 2015)
The essay analyses the corrupted and oppressive culture in Mexico, whose origins, according to the presented hypothesis, is the defeat of the Aztecs by Hernan Cortes. The characteristics of this culture were determined by the personal interests of the conquistadores, their customs, and their duties to the crown of Spain, as well as the reaction of the defeated: to the destruction of the best of the civilisations of the Anáhuac, was added the worse of the Spanish culture. As a result, during several centuries, the Spanish have promulgated the propaganda of the “civilisation of the Indians”, when they themselves and their descendants, were not at all prepared or capacitated to civilise anybody, and the forced Christianization was rather a pacification of the Indians, leaving the new society (authorities, church and population) in a social, economic and political stagnation. Cultural forms that still hold back the development of the country.